KONFLIK DI JOS, NIGERIA DAN KEAMANAN MANUSIA - , Maya Elfrida Sianipar, Drs. Muhadi Sugiono, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Security used to be connected with the military power, whose threats were the attacks from other countries. However after the Cold War ended, those kind of threats were changing into poverty, hunger, disease, and disaster. These threats put the human as the focus, which need the human-focused security, known as the human security. Those threats can potentially cause the internal conflicts in a country. The economic problem becomes the trigger of the most of the internal conflicts, which makes the condition of human security worse, and it continues even when the conflict is over. Nigeria is known as a country where there are some internal conflicts inside, and in one of its area, name Jos, there is still an internal conflict between the indigenes and the settlers that causes thousands casualties, lost of houses, and any other bad impact. According to that condition, this thesis aims to analyze the influence of the conflict in Jos towards the human security since the years of 2001 until 2010. This thesis is analyzed by using the relationship between the concept of human security and conflict. After the analysis, it is known that the conflict in Jos has threatened the human security, especially the community and personal security of both indigenes and settlers, not only one of them. The government who has the main responsibility, together with the non-government actors that oblige to help the government to create the human security, has made some efforts to solve the problem, but those efforts are failed. It is because there is no problem solving done through an empowerment efforts of the victims, which is seen by the human security concept as one of the important steps to achieve the human security.